Analysis of Budget Realization to Assess the Effectiveness and Efficiency of the Social Rehabilitation Sector of Children and the Elderly: (Bogor Regency Social Service) - Karinna, Karinna Tri Maharani; Rizqi, MN; Masruri, M Anwar (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze budget realization to evaluate the effectiveness and efficiency of financial management in the Social Rehabilitation Sector for Children and the Elderly at the Bogor Regency Social Services Office during the 2022–2024 period. Using qualitative descriptive methods, this study found that these programs consistently achieved high effectiveness, with 100% achievement of physical targets each year. Budget utilization was also classified as "very efficient," with an efficiency ratio of 10.75% in 2022 and 10.31% in 2023, although this decreased slightly to 13.91% in 2024. The results indicate that the program was generally implemented effectivelya nd efficiently. Keywords: Budget Realization; Effectiveness; Efficiency; Social Rehabilitation.